2009
DOI: 10.1007/s00497-009-0096-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and cytological development and starch accumulation in hermaphrodite and staminate flowers of olive (Olea europaea L.)

Abstract: In olive (Olea europaea L.), the formation of functionally staminate flowers rather than fully functional hermaphrodites is one of the major factors limiting fruit set, as flowers with aborted pistils are incapable of producing fruit. Studies conducted on various angiosperm species have shown a correlation between flower abortion and starch content. Thus, it is important to know if starch content plays a role in regulating pistil development in olive and if so, what mechanism regulates starch distribution. Cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 34 publications
5
39
0
Order By: Relevance
“…We found that the starch granules in the testa, endosperm, and embryo accumulated mainly in the plastids and were spherical, ellipsoidal, or irregular in shape. The starch granules proliferated mainly via middle constriction and the formation of a middle plate, similar to the mechanisms observed in seeds of wheat and rice [15][16][17]. We also observed chloroplasts in both the testa and endosperm during early development, some of which went on to accumulate starch granules and become amyloplasts.…”
Section: Formation and Accumulation Of Starch Granules In Different Tsupporting
confidence: 85%
See 1 more Smart Citation
“…We found that the starch granules in the testa, endosperm, and embryo accumulated mainly in the plastids and were spherical, ellipsoidal, or irregular in shape. The starch granules proliferated mainly via middle constriction and the formation of a middle plate, similar to the mechanisms observed in seeds of wheat and rice [15][16][17]. We also observed chloroplasts in both the testa and endosperm during early development, some of which went on to accumulate starch granules and become amyloplasts.…”
Section: Formation and Accumulation Of Starch Granules In Different Tsupporting
confidence: 85%
“…There are also some reports of a C-type starch granule with a diameter of less than 5 µm in endosperm tissues [13]. The starch granules in the endosperm tissues of wheat, rice, and angiosperm ovules develop from plastids [14][15][16]. However, it has also 6 ISRN Botany been proposed that they develop from mitochondria [14].…”
Section: Formation and Accumulation Of Starch Granules In Different Tmentioning
confidence: 99%
“…The importance of starch reserves in the pistil for the reproductive process has been previously reported in different plant species, as one of the major determinants of ''flower quality'' (Rodrigo and Herrero 1998;Rodrigo et al 2000;Alcaraz et al 2010). Starch is also important for pollen tube growth (Herrero and Dickinson 1979) and ovule fate and subsequent fruit set (Rodrigo and Herrero 1998;Rodrigo et al 2000;Reale et al 2009). …”
Section: Introductionmentioning
confidence: 93%
“…Samples were fixed in 5 % glutaraldehyde in 0.075 M sodium cacodylate buffer, pH 7.2, and post-fixed in 1 % (w/v) OsO 4 in 0.075 M sodium cacodylate buffer for 1.5 h. Samples were then dehydrated in increasing concentrations of ethanol and embedded in resin (Epon, 2-dodecenylsuccinic anhydride and methyl nadic anhydride mixture) (Reale et al, 2009). Semi-thin sections (1-2 µm) were cut with an ultramicrotome equipped with a glass blade, stained with toluidine blue and observed under a light microscope.…”
Section: Area Dry Mass (Adm) Chlorophyll (Chl) Content and Histo-anamentioning
confidence: 99%